Peru: Potential demand for cassava - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Price and trade, credit, research, and extension policies and their impact on agriculture in Peru are analyzed. The status of cassava consumption, production, and distribution is reviewed to determine potential and projected demand. Time series data and results of a household survey conducted by CIAT (1986) were used to calculate the effects of income, prices, and urbanization trends on the per capita consumption of cassava. Agriculture has been adversely affected by policy-induced distortions. By the year 2000, cassava production will have to expand by ca. 20,000 t, just to meet the demand due to population growth. In the humid forest areas, cassava is a major staple, competing favorably with other crops even under the present policies. To make fresh cassava from the humid forests available for urban consumers, CIAT's new conservation technology will have to be introduced; the project's success also depends on infrastructure development. The potential demand for cassava chips for animal feed will become effective if the support price already established by the Government is set as a fixed proportion (75 percent) of the price for yellow maize. (CIAT)